Electives in the medical curriculum as applicable to biochemistry: impacts and insights of medical students - Sushma BJ; Sumit Parashar; Raghvendra Saini; Heeralal Kumawat; Parduman Singh; Balvir Singh Tomar; Sandhya Mishra; Priyanka BJ (BMC Medical Education)
Abstract Introduction The ever-evolving landscape of medical science necessitates a curriculum that fosters specialized knowledge and expertise. Electives in Biochemistry offer a pivotal opportunity for medical students to explore the intricacies of biochemical processes, diagnostic technologies, and therapeutic interventions. By delving into specific areas of biochemistry, students can develop a nuanced understanding of the molecular mechanisms underlying human health and disease. The present study emphasised a newly adopted elective module schedule designed by department of biochemistry, at the National Institute of Medical Sciences and Research and also the present study assessed the insights and performance of medical students following elective postings. Materials and methods A combined qualitative and quantitative observational study was conducted in the Department of Biochemistry, NIMS & R, Jaipur. The study involved 45 students who are in phase III, part I of the MBBS Program in the Biochemistry Department. The students were divided into three small groups BE1, BE2 and BE3, with 15 students in each group, selected via a randomized lottery system. A newly adopted elective module was implemented, a pre-test and post-test were conducted and the scores obtained were compared for statistical significance. The students insights into electives were gathered via open-ended and closed ended questions. A Likert scale was used for scoring the closed -ended questions. Results All the Participants were assessed with the pre and post-test survey which assessed their overall impression of the elective course. Compared to pre-test results, the post-test demonstrates an improved impression of electives which was statistically significant (p < 0.0001). A total of 33.33% of the students had pre-test scores < 40% and none of the students had < 40% in the post-test. The mean scores obtained in the post-test were significantly higher than mean pre-test scores (p < 0.001). A total of 82.3% strongly agree that the newly adopted electives help in understanding the importance of Biochemistry, 73.33% strongly agreed that electives increased critical thinking and, 77.78% strongly agreed that electives increased the interest in the topic, 68.89% strongly agreed that time allocated for electives was adequate, 66.67% strongly agreed that electives enhance the knowledge in the subject, 64.45% strongly agree that electives encourage the understanding of the applied aspect of the topic, 82.3% strongly agreed that electives enhanced interest in the research project. Furthermore, 62.22% strongly agreed that electives encouraged them to pursue postgraduate programs in Biochemistry. Conclusion The introduction of the elective module in biochemistry has yielded promising results, fostering a deeper understanding and appreciation of the subject among medical students. The significant improvement in students’ performance and enthusiasm is a test of the module’s effectiveness. Ultimately, this initiative has the potential to nurture a new generation of medical professionals with a strong foundation in biochemistry.